Validation of a new portable system containing both FeNO analysis and spirometry measurement - Li, Yong; Huang, Ke; Li, Wei; Peng, Yaodie; Tang, Xingyao; Yang, Ting (Frontiers in Medicine, 2023)
Introduction: Pulmonary function tests and FeNO measurements are widely used for the diagnosis and management of respiratory diseases. They are used to evaluate airway limitation and respiratory inflammation. Standard spirometers and nitric oxide (NO) analyzers are widely used in hospitals.However, their high price has made some hospitals in underdeveloped areas unable to afford or purchase these devices. The development of a new portable system (SUNVOU TM2125) combining FeNO measurement and spirometry provides additional possibilities for optimizing the diagnosis and management of respiratory diseases. However, its accuracy needs further validation.The FeNO analysis component of SUNVOU TM2125 was compared with that of a widely used NO analyzer (NIOX VERO). The spirometry component of the TM2125 was compared with a standard spirometer (Jaeger MasterScreen) for pulmonary parameters such as FEV1, FVC, FEV1/FVC, and PEF. Pearson correlation and Bland-Altman plots were used to evaluate the agreement between the devices.Results: FeNO values measured using TM2125 were higher than those measured using VERO, with a mean difference of 1.8 ppb. There was a strong correlation between FeNO values measured using the two devices (r=0.988, p<0.001). Bland-Altman plots showed a high degree of agreement between the two devices, with 93.3% of values within the 95% confidence interval range. The spirometric parameters (FEV1, FVC, FEV1/FVC, and PEF) measured using the TM2125 were lower than those measured using the MasterScreen. Good correlations were observed between the values measured using the TM2125 and MasterScreen (r>0.9). Based on the Bland-Altman plots, there was a high degree of agreement between the devices.The accuracy of FeNO and spirometry measurements using SUNVOU TM2125 was validated. This can help improve the diagnosis and monitoring of chronic respiratory diseases in underdeveloped countries.